BENTUK PENYAJIAN DAN STRUKTUR MUSIK TATUNG PANGALANGOK NEK ITAPM PADA PERAYAAN CAP GO MEH - Yanuar Dwi Adi Prabowo; Imam Ghozali; Nurmila Sari Djau (Universitas Tanjungpura, 2021)
AbstractThis research is motivated by the uniqueness of the Pangalangok Nek Itapm tatung group. Tatung art is a tradition of the Chinese community, but in the Pangalangok Nek Itapm group all members are of the Dayak ethnicity. This study uses a descriptive-exploratory method, with an anthropological approach. Data obtained from interviews, observations, and documentation. The data validity technique used source triangulation and observation extension. The data in this study were analyzed using Miles and Huberman's theory. The results of this study indicate that the uniqueness lies in the special rituals and forms of presentation. The special ritual of the Panglangok Nek Itapm group uses a unique dish, namely using a sacred dish, namely blood, ancak, pahar, kalangkang, plain poek, native chicken eggs, tumpi', saba', tangkin, rice, and chicken, in This presentation is rarely encountered in special rituals in other tatung groups. In the form of its presentation Pangalangok Nek Itapm has a costume and dress that uses hornbill head, ruai feathers as head decoration, keris as a sword to be stabbed into the body of the tatung, deer antlers to hang on the neck as a unique decoration of the Pangalangok Nek tatung group Itapm.Keywords: Presentation Form, Tatung Pangalangok Nek Itapm Group